TILTED AIR SPARGED FORWARD OSMOSIS MODULE SYSTEM FOR FOULING CONTROL IN PRODUCED WATER TREATMENT - MOHD HIZAM, SHAFIQ (2019)
During oil and gas production, a large amount of waste called produced water (PW) is generated, which would be harmful to the environment if not treated properly. Forward osmosis (FO) as an alternative treatment seems promising due to its high salt rejection and low fouling propensity thus making FO suitable as a standalone unit with minimum pretreatment.